2013
DOI: 10.1177/0886260513505148
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Role Identification and Violent Victimization

Abstract: Although sex-role identification has been found to be associated with crime and delinquency, the link between sex-role identification and violent victimization has remained largely unexplored. Using the Add Health data, this study examines sex-role identification and its relationship to violent victimization. The findings suggest that masculinity increases the risk of violent victimization for males, but does not for females. Other differences in risk factors across gender were also found. These findings indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 70 publications
1
1
0
Order By: Relevance
“…Our previous report also confirmed many other findings from studies of associations of heightened traditional masculinity, or toxic masculinity as it is sometimes called, with getting into fights, acting delinquently, being expelled from schools, running away from home, and heavier use of drugs and alcohol (Daigle & Mummert, 2014; Wilkinson et al, 2018). Other studies have shown heightened suicidal ideation or attempts among HTM males (Coleman, 2015b; Pirkis et al, 2016) and earlier introduction into sexual activity (Udry & Chantala, 2004).…”
Section: Introductionsupporting
confidence: 87%
“…Our previous report also confirmed many other findings from studies of associations of heightened traditional masculinity, or toxic masculinity as it is sometimes called, with getting into fights, acting delinquently, being expelled from schools, running away from home, and heavier use of drugs and alcohol (Daigle & Mummert, 2014; Wilkinson et al, 2018). Other studies have shown heightened suicidal ideation or attempts among HTM males (Coleman, 2015b; Pirkis et al, 2016) and earlier introduction into sexual activity (Udry & Chantala, 2004).…”
Section: Introductionsupporting
confidence: 87%
“…Boys might resort to such misbehaviors to demonstrate their masculinity. By doing so, they may inadvertently place themselves in a position where they are more likely to be victimized (Daigle & Mummert, 2014). Physically violent activities enable boys to enhance This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Gender Invariancementioning
confidence: 99%